Valorizing Plastic Wastes and Textile Sludge as Composites - T. Raghunathan (Recent Progress in Science and Technology Vol. 9, 2023)
The textile industry is a major source of water pollution in the Tiruppur region of Tamil Nadu, India. The strict implementation of effluent treatment plants in major textile industries, as well as common effluent treatment plants for small scale industries, has helped to mitigate the problem. However, the sludge produced as a result of the treatment of textile industry effluent poses storage and disposal issues due to high concentrations of heavy metals, sulphates, and chlorides. When sludge is kept in open yards and dumped in landfills, these chemicals and heavy metals once more constitute a major threat to the environment. Once more, these substances erode into surface and rainwater. So there is a cycle of difficulties caused by both textile industry effluent and treatment plant sludge of textile industry. Thus, there are several studies being conducted on a global scale to incorporate the sludge into building materials. Waste plastic may be the apt binder for Textile sludge. The attempts to include sludge as an inert substance into concrete using different types of binders, including cement, geopolymer, and plastic, are discussed in this work. Plastic products often break down into micro plastics that can pollute ecosystems and harm bio-life. This study demonstrates a modest advance in attempts to encapsulate textile sludge using spent oil and waste polypropylene and polyethylene plastic in various ratios for valorizing.